Immunohistochemical and Molecular Characterization of Endometrial Stromal Sarcomas - Sneha Subbaraya; Sudha S Murthy; Sandhya Devi G (SAGE Publishing, 2020)
Introduction: Endometrial stromal sarcomas (ESSs) are rare and characterized by translocations t(7;17)(p15;q11.2) and t(10;17)(q22;p13), resulting in JAZF1-SUZ12 and YWHAE-FAM22 gene fusions used for defining low-grade (LG-ESS) and high-grade (HG-ESS) tumours. Aim: The objective of the study was to characterize ESSs using immunohistochemical and molecular markers. Material and Methods: Patients diagnosed as having ESSs between January 2014 and December 2018 were included in the study. The slides were reviewed along with a panel of immunohistochemical markers, CD10, cyclin D1, oestrogen receptor (ER) and progesterone receptor (PR), Ki67, and vimentin and classified according to World Health Organization (2014) criteria into LG-ESS, HG-ESS, and undifferentiated uterine sarcoma (UUS). Molecular characterization was performed by fluorescence in situ hybridization using relevant probes. Results: Over a 4-year period, 552 cases of endometrial malignancies were reported, 10 of which were ESS (1.8%). Of these, 5 were LG-ESS, 3 HG-ESS, and 2 UUS. CD10 was 100% sensitive and 75% specific for LG-ESS. Oestrogen receptor and PR were 100% specific but less sensitive (80%) for LG-ESS. Forty per cent (2/5) of LG-ESS demonstrated JAZF1-SUZ12 gene rearrangement. All 3 cases of HG-ESS showed diffuse strong cyclin D1 (>70% nuclei) positivity and were negative for cluster differentiation 10, ER, and PR and demonstrated YWHAE gene rearrangement. None of the UUS cases demonstrated this gene rearrangement. Conclusion: Endometrial stromal sarcomas are rare tumours (1.8% in this study). JAZF1-SUZ12 and YWHAE-FAM22 gene rearrangement helps in accurate characterization of ESS and can be used as diagnostic tools especially when the diagnosis is unclear or difficult. Cyclin D1 can be used as an adjuvant immunomarker for YWHAE gene-rearranged HG-ESS.